A nanoreactor based on SrTiO3 coupled TiO2 nanotubes confined Au nanoparticles for photocatalytic hydrogen evolution. (13th January 2020) - Han, Bin; Wu, Liangpeng; Li, Juan; Wang, Xiaoyang; Peng, Quanming; Wang, Nan; Li, Xinjun
Abstract: A TiO2 nanotube-based nanoreactor was designed and fabricated by facile two steps synthesis: firstly, hydrothermal synthesized SrTiO3 was deposited on TiO2 nanotubes (TiO2 NTs). Secondly, the Au nanoparticles (NPs) were encapsulated inside the TiO2 NTs followed by vacuum-assisted impregnation. The as-synthesized composites were characterized using Transmission electron microscopy (TEM), X-ray powder diffraction (XRD), X-ray photoelectron spectroscopy (XPS), Photoluminescence spectra (PL) and Ultraviolet–visible absorption spectroscopy (UV–vis). The photocatalytic performance was evaluated by the hydrogen evolution reaction. The results revealed that the SrTiO3 modified TiO2 NTs confined Au NPs (STO-TiO2 NTs@Au) achieved an enhanced hydrogen evolution rate at 7200 μmol h −1  g −1, which was 2.2 times higher than that of bald TiO2 NTs@Au at 3300 μmol h −1  g −1 . The improved photocatalytic activity could be attributed to the synergistic effect of the electron-donating of SrTiO3 and TiO2 NTs confinement. The as-designed nanoreactor structure provides an example of efficient carriers' separation photocatalyst. Graphical abstract: The SrTiO3 modified TiO2 NTs confined Au NPs nanoreactor was designed and fabricated. It achieved an enhanced hydrogen evolution rate at 7200 μmol h −1  g −1, which was 2.2 times higher than that of bald TiO2 NTs@Au at 3300 μmol h −1  g −1 . The improved photocatalytic activity could be attributed to the synergistic effect of the electron-donating of SrTiO3 and TiO2 NTs confinement. Image 1 Highlights: SrTiO3 decorated TiO2 nanotubes confined Au nanoparticles were prepared. The nanoreactor displays excellent photocatalytic activity toward hydrogen evolution. SrTiO3 promotes the separation of charge carriers of nanoreactor and enhance HER.